2018
DOI: 10.1021/acsomega.8b02063
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide-Oligonucleotide Interfaces: Understanding Based on Electrochemical Oxidation of Guanines

Abstract: Investigation into the interactions between biomolecules DNA/RNA and carbon nanomaterials is very important for applications in bioassays and bioanalysis. Graphene and graphene oxide (GO) have been successfully adopted by exploiting the binding affinity difference between single-stranded oligonucleotides (ssDNA) and double-stranded oligonucleotides (dsDNA) to graphene sheets. In this work, we describe the electrochemical DNA oxidation with [Ru(bpy) 3 ] 2+ to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The Cy5 fluorophore probe is quenched by the tight electrostatic interaction due to the π,π-stacking between the nucleobases and GO. 25,29 Later, when the second amplified "N" gene RNAs under the LDT reaction are exposed to the quenched Cy5 probe solution, the Cy5 probe-RNA hybridization occurs due to their H-bond interactions compared to the previous electrostatic-π,π stacking bond of the quenched solution. This incident of fluorophore probe-RNA hybridization turned ON the quenched emission of the Cy5 fluorophore again by releasing its fluorescence at the wavelength of 660 nm.…”
Section: Demonstration Of Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…The Cy5 fluorophore probe is quenched by the tight electrostatic interaction due to the π,π-stacking between the nucleobases and GO. 25,29 Later, when the second amplified "N" gene RNAs under the LDT reaction are exposed to the quenched Cy5 probe solution, the Cy5 probe-RNA hybridization occurs due to their H-bond interactions compared to the previous electrostatic-π,π stacking bond of the quenched solution. This incident of fluorophore probe-RNA hybridization turned ON the quenched emission of the Cy5 fluorophore again by releasing its fluorescence at the wavelength of 660 nm.…”
Section: Demonstration Of Hypothesismentioning
confidence: 99%
“…By using this pioneering quenching capacity of GO, we execute our fluorometric multiple gene detection by ligationdouble transcription. [25][26][27][28][29][30][31][32][33][34] Our analysis exposes key features of multiple gene detection with high sensitivity and is a step towards a detection system with superior efficiency (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Both GO and rGO have strong interactions with single-stranded DNA (ssDNA) through hydrophobic and π-π stacking interactions [ 109 111 ]. However, functionalization with positively charged molecules is necessary for interactions with double-stranded DNA (dsDNA) to allow electrostatic interactions [ 112 114 ].…”
Section: Properties Of Graphene Oxide and Reduced Graphene Oxidementioning
confidence: 99%
“…To harness the properties of such interfaces for sensitive biosensing platforms, interactions of nucleic acids with graphene-based surfaces have been extensively studied in two regimes, i.e., physisorption and chemisorption [14]. The interfacing of DNA and graphene surfaces is often achieved by the simple mixing of DNA oligonucleotide solution with graphene solution (a liquid/liquid interface) to form DNA-graphene hybrids [15,16], and DNA self-assembly on graphene electrodes (a liquid/solid interface) [17]. Theoretical studies have confirmed π stacking interactions between hydrophobic DNA basepairs and graphitic carbon rings of graphene as a driving force of adsorption [18][19][20].…”
Section: Introductionmentioning
confidence: 99%